Managerial Accounting for Managers - Garrison Ray.H (MC Graw Hill, 2008)
Managerial Accounting for Managers, 1/e by Noreen/Brewer/Garrison is based on the market-leading text, Managerial Accounting, by Garrison, Noreen and Brewer. The Noreen book was created to serve customers who do not wish to teach the financial accounting-oriented content that is included in the Garrison book. Of our three books (the Brewer book, the Garrison book, and the Noreen book), the Noreen book is the most pure management accounting textbook. The other two books have greater amounts of financial accounting content.